Embedded Experts Supporting Instructional Practice of Faculty Transitioning from Industry to Academia. Issue 3 (3rd July 2022) - Garcia, Stephanie A.; Bonner, Emily P.; Nelson, Robin; Yuen, Timothy T.; Marone, Vittorio; Browning, JoAnn
Abstract: The transition from industry to academia can present unique challenges for new faculty members in STEM (Science, Technology, Engineering, and Mathematics) fields. Considering high drop, fail, withdraw (DFW) rates in undergraduate STEM courses and the need to increase the number of well-prepared graduates in these areas, it is important to better understand the needs of early-career faculty transitioning from outside of academia in order to support their development as effective scholars and educators. This study, which utilizes a Scholarship of Teaching and Learning (SoTL) framework, focuses on the experiences, views, and needs of two engineering faculty members who have recently moved from industry to academia. Findings inform practice and indicate a common lack of knowledge about new faculty's teaching requirements, a need for personalized support structures for incoming faculty members, and a shift toward active approaches to teaching students when such supports are provided. In this process, leveraging an embedded experts model and acknowledging and understanding students' needs through active listening emerged as important factors in faculty's growth and personal development during their first semester in academia.